Inspiration from Yewol for all of us - Amede, Tilahun; Dejen, A.; Gashaw, Tsehay; Yimam, G. (International Crops Research Institute for the Semi-Arid Tropics, 2019)
Five years ago, communities in the dry highlands of the Yewol mountains found it difficult to grow even their staple crops. In the rainy season, rainwater gushed down the slopes eroding the soil. Free grazing of cattle and unreliable rain affected the productivity so much that crops began to dwindle along with their livestock. Migration was the only way out for some. Food shortage stalked the residents and it still is a reality for some.